2018
DOI: 10.1037/gpr0000170
|View full text |Cite
|
Sign up to set email alerts
|

A Historically Based Review of Empirical Work on Color and Psychological Functioning: Content, Methods, and Recommendations for Future Research

Abstract: Empirical work on color and psychological functioning has a long history, dating back to the 19th century. This early research focused on five different areas: Arousal, physical strength, preference, time perception, and attention. In the present paper, I overview the relations observed in this early research, and detail methodological weaknesses therein. I then trace subsequent 20th and 21st century developments in these research areas, in terms of both content and methods. Finally, I extend the review to cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 282 publications
(593 reference statements)
0
33
0
Order By: Relevance
“…Our results suggest that the latter seems more likely. On the other hand, Elliot (2015Elliot ( , 2019 emphasized that only a precise combination of luminance, chroma, and hue is expected to produce intellectual impairment. According to this line of reasoning, simply reading the word red should not elicit any cognitive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the latter seems more likely. On the other hand, Elliot (2015Elliot ( , 2019 emphasized that only a precise combination of luminance, chroma, and hue is expected to produce intellectual impairment. According to this line of reasoning, simply reading the word red should not elicit any cognitive effects.…”
Section: Discussionmentioning
confidence: 99%
“…In psychology, publication bias is rife (Ferguson & Brannick, 2012;Ferguson & Heene, 2012), raising the possibility that many more studies were conducted and found evidence of no difference. To address this as well as to reduce the analytical flexibility that yields many false positives, preregistration is an absolute must for this literature going forward (Nosek et al, 2018), as are the color-related methodological prescriptions laid out by Elliot (2019).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Perhaps as a result of the unwarranted generalizations made in the literature, typically studies do not use the same exact hue as any previous study, and at this point there is little idea whether this accounts for discrepancies in results. Given the existence of this as well as the multiple other methodological issues detailed by Elliot (2019), researchers in the area have a lot of work ahead of them if the literature is to provide reliable and useful results.…”
Section: Moving Forwardmentioning
confidence: 99%
See 2 more Smart Citations